PERENCANAAN SKENARIO DALAM PENGEMBANGAN BISNIS KULINER HALAL DI PULAU LOMBOK – NUSA TENGGARA BARAT - Dewi Rispawati; Vidya Yanti Utami (Master of Management, Mataram University, 2019)
This research is describes the scenario planning for the development of halal culinary business on Lombok Island - West Nusa Tenggara Province. The purpose of this research is to create a scenario planning model in dealing with existing problems. This is descriptive research with data collection methods using case studies. Data collection is using observation, interview and documentation and data analysis is using scenario planning analysis. The focus of this research is about the stages in scenario planning using the TAIDA method consisting of Tracking, Analyzing, Imaging, Deciding and Acting. The results of the research showed that Lombok Island - West Nusa Tenggara was still not maximal, in developing halal culinary business, because there are several obstacles faced by the culinary businessmen and the government, so that good planning is needed to analyze and provide a scenario for the future conditions of the halal culinary business. This research is expected to provide an overview of the development of halal culinary business in Lombok Island in the future and minimize the consequences and possible impacts of developing a halal culinary business and to sharpen a strategy.Keywords : Scenario Planning, Business Development, and Halal Culinary.